Robot‐assisted salvage seminal vesicle excision for isolated recurrence after low‐dose‐rate prostate brachytherapy. (14th September 2021) - Langley, Stephen; Eden, Christopher; Perry, Matthew; Patil, Krishna; Moschonas, Dimitrios; Higgins, Donna; Deering, Claire; Laing, Robert; Perna, Carla; Khaksar, Sara; Uribe‐Lewis, Santiago; Uribe, Jennifer
Abstract : Objectives: To report clinical and functional outcomes for patients who have undergone salvage robot‐assisted seminal vesicle excision (RA‐SVE) for the focal treatment of isolated seminal vesical (SV) recurrence after treatment for prostate cancer by low‐dose‐rate brachytherapy. Patients and Methods: Patients with rising prostate‐specific antigen (PSA) after low‐dose‐rate prostate brachytherapy (LDR‐PB) underwent multi‐parametric magnetic resonance imaging (mp‐MRI) of the prostate and 11 C‐Choline or 68 Ga‐prostate‐specific membrane antigen ( 68 Ga‐PSMA) positron emission tomography/computed tomography (PET/CT) scan, followed by targeted transperineal biopsy of the prostate and SVs. Isolated SV recurrence were identified in 17 (0.38%) LDR‐PB patients. These 17 patients were offered RA‐SVE. Results: The median total operative time was 90 min and blood loss 50 mL with no postoperative transfusions required. The median hospital stay was 1 day. No intra‐ or postoperative complications were documented. Continence status was unaffected, no patient required urinary pads. Postoperative pathology confirmed SV invasion in all specimens. Surgical margins were positive in seven (41%) patients. All patients had at least one positive imaging study, although three (18%) mp‐MRI and five (29%) PET/CT assessments were negative. One (6%) pre‐SVE biopsy was also negative but with positive imaging. Salvage SVE failure, defined as three consecutive PSA rises or the need for further treatment, occurred in six patients of whom three had a positive margin. Overall failure‐free survival rates were 86%, 67%, and 53% at 1, 2, and 3 years after SVE, respectively. Conclusions: Salvage RA‐SVE appears to be a safe focal treatment, with very low morbidity, for patients with localised SV recurrence after LDR‐PB. It permits deferral of androgen deprivation therapy in selected patients. Bilateral SVE is mandatory. This surgical option should be considered in patients with isolated prostate cancer recurrence to the SV.